On some difference sequence spaces of fuzzy numbers - Et, Mikail; Savas, Ekrem; Altinok, Hifsi (Springer, 2016)
In this paper, using the difference operator of order m and a lacunary sequence , we introduce and examine some classes of sequences of fuzzy numbers. Furthermore, we study some of their properties like completeness, solidity, symmetricity and convergence free. We also give some inclusion relations related to these classes.
Keywords: Fuzzy number; Difference sequence; Lacunary sequence